Propuesta de un formato electrónico de evaluación post-sismo para edificios en la ciudad de Guayaquil - Garces Cueva, Jinson Cristian (2023)
Guayaquil, Ecuador, faces a constant seismic threat due to its location in a zone of high seismic hazard. The devastating earthquake of magnitude 7.5 mw in 2016 evidenced the need for an efficient methodology to assess structural damage to buildings. This work proposes an electronic format for post-seismic evaluation for city buildings, adapting national and international formats. It was designed in the Excel tool, streamlining decision-making and guaranteeing compliance with current regulations and structural concepts, giving an assessment of traffic lights (green, yellow and red). The research combines quantitative and qualitative methods to analyze the seismic effects in a building in Guayaquil, collecting numerical data and perceptions of affected people. It seeks to fully understand earthquakes and improve construction strategies to mitigate risks. The building studied consists of 4 floors of reinforced concrete, and the post-seismic evaluation will identify structural damage and propose reinforcements according to current regulations. Elements and pathological damages in the building are mentioned, as well as the importance of considering geotechnical and non-structural threats in the seismic analysis. The electronic format is correct by means of a score evaluation qualifying by traffic lights, which it defines as green (Temporary-Operational), yellow (Restricted Use), red (do not enter).